The Sources of the Gender Gap in Economics Enrolment - Mirco Tonin; Jackline Wahba (Institute for the Study of Labor (IZA), 2014)
In many countries there is a considerable gender gap in enrolment for a bachelor's degree in Economics, arguably an important stepping stone towards positions of influence in policy making and occupations paying relatively high wages. We investigate the sources of this gap by looking in detail at the university admission process in the UK. We use a 50 percent random sample of administrative data covering all university applications in 2008 and find no evidence of universities discriminating against female applicants. What we find is that girls are less likely to apply for a bachelor's degree in Economics to start with, even if once they apply their likelihood of enroling is the same as for boys. Girls are less likely to study Maths in high school and this may deter them from applying to study Economics at the university level. However, even among those who have studied Maths, females are less likely to apply than males, suggesting that differences in the choice of A level subjects cannot explain the whole gap.
Keywords: I21; I23; I28; J24; 330; education; economics; gender; discrimination; pay gap